Quantification of Vitamin D at Different Levels of Clinical Worsening of COVID-19 - Tsun, Lai Y.; Bibo, Thaciane Alkmim; Affonso Fonseca, Fernando Luiz; da Veiga, Glaucia Luciano; Macedo Gaiatto, Ana Carolina; de Godoy Moreira e Costa, Nicolle; Raimundo, Joyce Regina; Perez, Matheus Moreira; Gascón, Thaís; Scorza, Fulvio Alexandre; Scorza, Carla Alessandra; Nader, Helena; et al. (Current Drug Metabolism, 2022)
Introduction and Aim: Vitamin D is the name given to a group of lipid-soluble steroidal substances of physiological importance in the body, especially in bone metabolism. The active form of vitamin D is believed to have immunomodulatory effects on immune system cells, especially T lymphocytes, as well as on the production and action of several cytokines and on the expression of potent antimicrobial peptides in epithelial cells that line the respiratory tract, playing an important role in protecting the lung from infections. The aim of this study was to assess vitamin D levels in patients with COVID-19 in healthcare service and to verify that these levels are adequate to protect the progression of this infection. Methods: The aim of this observational study was to evaluate the serum concentration of vitamin D in 300 patients suspected of being infected with COVID-19, treated at Basic Health Units (BHUs) and at the Hospital Complex in the municipality of São Bernardo do Campo. Results: 294 patients were included, 195 (66%) of which tested positive for COVID-19 and 99 (34%) negative for COVID-19. Among the patients in the positive group, 163 patients were in the mild group (84%); 22 patients in the moderate group (11%); 8 patients in the severe group (4%), and 2 patients in the deceased group (1%). Conclusion: For the patients in this study, no association was observed for the protective factor of vitamin D against COVID-19 infection, and its role in controlling the clinical staging of the disease was not verified.
Keywords: Vitamin D